Determinants of Saudi Arabian women’s luxury fashion brands purchase intention: Mediation effect of cognitive-affective model / Amani Adnan M.Aqeel - M.Aqeel, Amani Adnan (Institute of Graduate Studies, UiTM, 2016)
Saudi Arabia, a country that has often been described as traditional and conservative, has been experiencing rising consumption of luxury brands lately. This is indeed an area that is still underexplored as the consumption behaviour of Saudi women toward luxury fashion brands have not been given much attention in the literature. As luxury goods are products that have intrinsic values and high social standing, both rational and emotional variables must be considered in the study of consumer behaviour and the cognitive-affective model is one of the theoretical bases in understanding such purchase intention. The cognitive-affective model has been used to understand the purchase intention of goods but very little of its application is seen in the context of luxury goods where perceived quality and emotional value are incorporated. As such, the mediating effect of perceived quality and emotional value as suggested by the model is the emphasis of this study as this is an area that has yet to be pursued extensively in existing literature. In line with this, the main objective of this study was to determine the relationship between the social status of women consumers and their purchase intention of luxury brands in Saudi Arabia…